Ответы и объяснения

2013-03-23T18:01:41+04:00

1) (\frac{a}{a-b}-\frac{a}{a+b})\frac{a+b}{a}=\frac{2ab(a+b)}{(a-b)(a+b)a}=\frac{2b}{a-b}

2) (\frac{b}{a-b}-\frac{b}{a+b})\frac{a-b}{b}=\frac{2b^{2}(a-b)}{(a-b)(a+b)b}=\frac{2b}{a+b}

3) (\frac{a}{c}+\frac{c}{a}-2)\frac{1}{a-c}=\frac{(a-c)^{2}}{ac(a-c)}=\frac{a-c}{ac}

4) (\frac{a}{b}+\frac{b}{a}+2)\frac{1}{a+b}=\frac{(a+b)^{2}}{ab(a+b)}=\frac{a+b}{ab}

5) (\frac{3c+1}{c-1}+c)\frac{1}{c+1}=\frac{(c+1)^{2}}{c(c-1)(c+1)}=\frac{c+1}{c(c-1)}

Я більше не можу. Стомився від кількості. Вирішіть другу половину зтось інший.